2019
DOI: 10.2478/prilozi-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maternal Levels of Vitamin D and Adiponectin on Anthropometrical Measures and Bone Health in Offspring

Abstract: Background: From the conception onward, certain parameters associated with maternal health may affect foetal body composition, growth and bone mineral content. The objective of the study was to determine the association between maternal vitamin D and adiponectin status with the anthropometrical measures of newborns, and bone health status measured by Quantitative Ultrasound (QUS) at birth. Methods: Circulating 25OHD and adiponectin concentration were measured in 73 pregnant women. Correlations with the anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The review covered two research clusters of healthy pregnant women. One included data collected in the ‘My Milk’ research project (‘The role of human milk in the development of breastfed child’s intestinal microbiota’) ( 17 , 31 , 32 ). We only included publications with a full study sample ( 17 ), as two references refer to a smaller subsample size ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review covered two research clusters of healthy pregnant women. One included data collected in the ‘My Milk’ research project (‘The role of human milk in the development of breastfed child’s intestinal microbiota’) ( 17 , 31 , 32 ). We only included publications with a full study sample ( 17 ), as two references refer to a smaller subsample size ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported a negative association with offspring total BMD (with no difference in lumbar BMD) [ 17 ]. Six studies found no association between maternal vitamin D status and bone parameters from the neonatal period even to the age of 26 years [ 23 , 35 , 36 , 37 , 38 , 39 ]. In the four remaining studies, positive associations were found between maternal vitamin D status and offspring BMD [ 18 , 40 ], with sex-specific association in one study [ 41 ], as well as neonatal bone SOS [ 42 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In all of the included studies on maternal vitamin D status, authors assessed 25(OH)D concentrations [ 17 , 18 , 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In addition, in one study, 1,25(OH) 2 D concentrations were also assessed and its levels were similar across different levels of 25(OH)D [ 23 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations